Scientific production in Transcultural Nursing during the period 2007-2014 - Fátima Berchid-Martínez; Raquel Herrero-Hahn; César Hueso-Montoro (Universidad de Alicante, 2018)
The objective was to identify and analyze the scientific production on Transcultural Nursing in the international context in the period between 2007 and 2014. A literature review on the CINAHL and CUIDEN database was performed using the descriptor "Transcultural Nursing" and including only original or research articles published between 2007 and 2014. A documentary descriptive study of the selected literature was carried out using bibliometric indicators. A total of 155 articles were obtained. The profile of the publications is the one of works signed by 2 or three women authors who mainly belong to the nursing discipline and whose work reference institution is the university. Most of these studies were conducted in the United States, Brazil and Spain. They are fundamentally qualitative design studies that address as major thematic the experiences and beliefs regarding health or disease, the training of students and professionals, and their proceeding in the field of cultural diversity.